Molecular and isotopic evidence for the processing of starchy plants in Early Neolithic pottery from China. Issue 1 (December 2018) - Shoda, Shinya; Lucquin, Alexandre; Sou, Chi; Nishida, Yastami; Sun, Guoping; Kitano, Hiroshi; Son, Joon-ho; Nakamura, Shinichi; Craig, Oliver
Abstract Organic residue analysis of ancient ceramic vessels enables the investigation of natural resources that were used in daily cooking practices in different part of the world. Despite many methodological advances, the utilization of plants in pottery has been difficult to demonstrate chemically, hindering the study of their role in ancient society, a topic that is especially important to understanding early agricultural practices at the start of the Neolithic period. Here, we present the first lipid residue study on the Chinese Neolithic pottery dated to 5.0 k - 4.7 k cal BC from the Tianluoshan site, Zhejiang province, a key site with early evidence for rice domestication. Through the identification of novel molecular biomarkers and extensive stable isotope analysis, we suggest that the pottery in Tianluoshan were largely used for processing starchy plant foods. These results not only highlight the significance of starchy plants in Neolithic southern China but also show a clear difference with other contemporary sites in northern Eurasia, where pottery is clearly orientated to aquatic resource exploitation. These differences may be linked with the early development of rice agriculture in China compared to its much later adoption in adjacent northerly regions.